â€œNGOMBANGâ€: POTRET ANTROPOLOGIS MASYARAKAT PESISIR PEKALONGAN DALAM KARYA TARI - Hery Suwanto (Institut Seni Indonesia Surakarta, 2015)
Life of fishermen in Wonokerto Kulon, Pekalongan, Central Java owned a hard life. Theylived with a cycle rotation of life: monotoni. In the circle of nature, when the wind blows fromAsia continent through Indonesia region, made condition changed: waves more higher, wind blowsstronger and the sea more difficult to be sailed. People in Wonokerto called it as angin kombang.When angin kombang blowing from West, time become very valuable to brightening and cheerup, one of through the art of kendang pencak, a traditonal Javanese art of fighting. Kendang Pencak represent the art of self-defence but also can called as a self-defence dance, combining silatand dance accompanied by gamelan orchestra. the beat of kendang become a kind of beat representing a vital energy of fishermen life. Monotoni of fishermen life will lost because emerging eruption of new dynamics in their life. The creatorâ€™s empirical experience owned body dance and alsohave learned pencak silat and karate exploited to explore dance movement of kendang pencakbecome kind of a new dance. â€œNgombangâ€ explore fisherman body: continuing monotoni motionsexpressing strength, mobility, and slow-softly movements. Exploration of the body combined bymotions of traditional martial art of kendang pencak supported by karate, yoga and tai-chi.These elements represent in body dance of dancers.Keyword: fishermen, kendang pencak, monotoni.